Retrospective Medium-Term Forecast of a Catastrophic Earthquake in Turkey in 2023 (02.06.2023, MW=7.7) Using the LURR Method - A. S. Zakupin; N. A. Sycheva (Геодинамика и тектонофизика)
Variations of the LURR (load-unload response ratio) earthquake medium-term forecasr parameter in combination with changes in seismotectonic deformation modes (STD) for the East Anatolian fault region, where catastrophic earthquakes occurred in February 2023 (06.02.2003, MW=7.8, 06.02.2003, MW=7.6) are considered. The depth of the earthquake catalog for the LURR method calculations was equal to 23 years, and estimates of STD modes were possible received since 1976. Calculations have shown satisfactory results in detecting LURR anomalies before strong earthquakes. Almost half of the anomalies occurred in the one and a half year period before the doublet, and are unambiguously associated as precursors. The precursors were recorded by two series of LURR parameter anomalies in 2021 and 2022, and the calculation areas in which they were recorded compactly cover the East Anatolian fault, including the epicenters of the earthquakes on February 6, 2023. The results of calculations using the LURR method were compared with the reconstruction data using the STD method. As a result, it was possible to build the dynamics of the earthquake preparation process in its final part – from the appearance of the LURR anomaly to the earthquake. At the same time, the period before the appearance of anomalies (since the 1976) was also taken into account. It is shown that during the period of abnormal LURR behavior (the forecast period), the most significant changes in the geodynamic regime were observed, as well as a sharp increase in total seismic activity.